An ethnographer in Parliament: politics, rituals, and ethical dilemmas - Mineiro, João. (EASA2020: New anthropological horizons in and beyond Europe, 2020)
his paper is based on an ethnography of the Portuguese Parliament, conducted between 2015 and 2018, and will discuss what socially characterizes the Portuguese MPs, how they organize themselves in a hierarchal and ritual world, and the ethical dilemmas the ethnographer faced in the fieldwork. Paper Long abstract: Assembleia da República is the house of the Portuguese Parliament. Studied mainly by political scientists and legal scholars, these analyses tend to ignore aspects such as the interactional dimension of politics, the meaning of rituals, and the symbolic aspects that organize everyday life. This paper is based on ethnographic fieldwork in the Portuguese Parliament, seeking to understand political representation in action and from within, thus going beyond institutional self-representations and media discourse. Firstly, I discuss how and why political representation is socially confined: largely dominated by educated men, coming from the largest urban areas and part of multiple political environments. Then, it is argued that the individual agency of the MPs can only be understood in the context of their insertion in a hierarchical and ritual world. Finally, it is contended that different class positions (Bourdieu, 1985; Friedman and Laurison, 2019) enhance or inhibit access and adaptation to the political field, where the unequal distribution of political capital, establishes a set of cultural boundaries between who is inside and who is outside. This research has been a quest with many dilemmas. The absence of a formal authorization could be reversed only by pursuing trust relations with people whose work I accompanied, safeguarding their own anonymity. In its turn, there were ethical implications in the making of the archive. What may and not may publicly be divulged - and how, with and whom? Lastly, I discuss the challenges involved when articulating ethical dilemmas with the epistemological ambition of the research.